Evaluating the role of the FUS/TLS-related gene EWSR1 in amyotrophic lateral sclerosis. - Couthouis, J.; Hart, M.P.; Erion, R.; King, O.D.; Diaz, Z.; Nakaya, T.; Ibrahim, F.; Kim, H.J.; Mojsilovic-Petrovic, J.; Panossian, S.; Kim, C.E.; Frackelton, E.C.; et al. (Human Molecular Genetics, 2012)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease affecting motor neurons. Mutations in related RNA-binding proteins TDP-43, FUS/TLS and TAF15 have been connected to ALS. These three proteins share several features, including the presence of a bioinformatics-predicted prion domain, aggregation-prone nature in vitro and in vivo and toxic effects when expressed in multiple model systems. Given these commonalities, we hypothesized that a related protein, EWSR1 (Ewing sarcoma breakpoint region 1), might also exhibit similar properties and therefore could contribute to disease. Here, we report an analysis of EWSR1 in multiple functional assays, including mutational screening in ALS patients and controls. We identified three missense variants in EWSR1 in ALS patients, which were absent in a large number of healthy control individuals. We show that disease-specific variants affect EWSR1 localization in motor neurons. We also provide multiple independent lines of in vitro and in vivo evidence that EWSR1 has similar properties as TDP-43, FUS and TAF15, including aggregation-prone behavior in vitro and ability to confer neurodegeneration in Drosophila. Postmortem analysis of sporadic ALS cases also revealed cytoplasmic mislocalization of EWSR1. Together, our studies highlight a potential role for EWSR1 in ALS, provide a collection of functional assays to be used to assess roles of additional RNA-binding proteins in disease and support an emerging concept that a class of aggregation-prone RNA-binding proteins might contribute broadly to ALS and related neurodegenerative diseases.